Avaliação de sintomas e cognições dissociativas e pós-traumáticas em crianças internadas em unidades pediátricas em Belém - PRAZERES, Itla das Neves (2019)
The Dissociative Disorders and Post-traumatic Syndromes generate changes in the individual‟s lives and its consequences change both the routine and cognitions of daily activities. It can be even more devastating when triggered and not properly diagnosed and treated in the infant stage. Several factors can be considered as sources of stress capable of triggering signs and symptoms associated with both psychological disorders. A long period of hospitalization, unresolved family conflicts, and genetic characteristics can be mentioned among such factors. In this context Nursing has a huge importance, representing a source of emotional support, offering health education, and evaluating hospitalized infants‟ needs as well as their families‟ needs. Thus, this study aimed to assess children and caregivers through international evaluation questionnaires in the search for evidence of dissociative symptoms and posttraumatic cognitions. It was also developed on the interest in expanding the understanding of such disorders in order to provide support to children and families. It is an evaluative quantitative study, which was developed in Pediatric Units of Hospitals in Belém. It assessed children and caregivers in the period from June to August 2016. As this study involves human subjects the conditions of the Ordinance 466/2012 of the National Health Council were followed. This study was relevant, since it has enlarged knowledge regarding the previously mentioned mental disorders. It was observed that contemporary society also plays an important role, which often ends allowing triggering conditions to take place. It was also found the importance of nursing in research and recognition process as well as in helping and guiding the family on their involvement in the health process of internalized children